The Role of Kainate Receptors in the Pathophysiology of Hypoxia-Induced Seizures in the Neonatal Mouse - Denise K. Grosenbaugh (Nature Portfolio, 2018)
Abstract Kainate receptors (KARs) are glutamate receptors with peak expression during late embryonic and early postnatal periods. Altered KAR-mediated neurotransmission and subunit expression are observed in several brain disorders, including epilepsy. Here, we examined the role of KARs in regulating seizures in neonatal C57BL/6 mice exposed to a hypoxic insult. We found that knockout of the GluK2 subunit, or blockade of KARs by UBP310 reduced seizure susceptibility during the period of reoxygenation. Following the hypoxic insult, we observed an increase in excitatory neurotransmission in hippocampal CA3 pyramidal cells, which was blocked by treatment with UBP310 prior to hypoxia. Similarly, we observed increased excitatory neurotransmission in CA3 pyramidal cells in an in vitro hippocampal slice model of hypoxic-ischemia. This increase was absent in slices from GluK2−/− mice and in slices treated with UBP310, suggesting that KARs regulate, at least in part, excitatory synaptic neurotransmission following in vivo hypoxia in neonatal mice. Data from these hypoxia models demonstrate that KARs, specifically those containing the GluK2 subunit, contribute to alterations in excitatory neurotransmission and seizure susceptibility, particularly during the reoxygenation period, in neonatal mice. Therapies targeting KARs may prove successful in treatment of neonates affected by hypoxic seizures.